Exploitation of biotic inducers for the management of important foliar diseases of sunflower (Helianthus annuus L.): Exploitation of biotic inducers for the management of important foliar diseases of sunflower (Helianthus annuus L.) - L RAJENDRAN; T SELVAKUMAR; S HARISH; R SASIKALA; T KALAIMAGAL; PL VISWANATHAN (Journal of Oilseeds Research, 2023)
Sunflower (Helianthus annuus L.) is a unique crop grown for human consumption as edible oil and also for ornamental use. It has become a popular cut flower, easy to grow under varied climatic conditions requires 672.4 mm water requirement during growing season. Sunflower crop is native to North America and as of now we have the varieties, hybrids developed from the huge germplasm collections maintained at ICAR-Indian Institute of Oilseeds Research and also at co-ordinating centres under AICRP on sunflower situated at different agro-climatic regions of India. During the crop growing period, many fungal and viral diseases start affecting the crop from early stage up to flowering and milky stage leads to drastic losses in seed yield. In particular, necrosis, leaf spot and powdery mildew diseases are causing drastic yield losses in the cultivation. In this study, we have attempted the biotic inducers as seed treatment and foliar spray against this disease as an alternative to fungicide.